Epidemiologic Characteristics, Prognostic Factors, and Treatment Outcomes in Primary Central Nervous System Lymphoma: A SEER-Based Study - Tang, Dongsheng; Chen, Yue; Shi, Yuye; Tao, Hong; Tao, Shandong; Zhang, Quan’e; Ding, Banghe; He, Zhengmei; Yu, Liang; Wang, Chunling (Frontiers in Oncology, 2022)
Objective: To study the clinical characteristics, prognostic factors and treatment outcomes in patients with primary central nervous system lymphoma (PCNSL). Materials and Methods: The data of total 5166 PCNSL patients diagnosed between 2000 and 2018 from the Surveillance, Epidemiology, and End Results (SEER) database was obtained. Results: The mean age was 63.1±14.9 years, with a male to female of 1.1:1.0. The most common histologic subtype was diffuse large B-cell lymphoma (DLBCL) (84.6%). The 1-, 3-, and 5-year overall survival (OS) were 50.1, 36.0 and 27.2%, respectively and the corresponding disease-specific survival (DSS) were 54.4, 41.3 and 33.5%, respectively. Multivariate analysis with Cox regression showed that the race, sex, age, marital status, surgical resection, and chemotherapy were independent prognostic factors for OS and DSS, but radiotherapy was only for OS. Nomograms specially for DLBCL were established to predict the possibility of OS and DSS. The concordance index (C-index) of OS and DSS were 0.704 (95% CI 0.687-0.721) and 0.698 (95% CI 0.679-0.717), suggesting the high discrimination ability of the nomograms. Conclusion: Surgical resection or/and chemotherapy was favorably associated with better OS and DSS. However, radiotherapy did not benefit to OS and DSS in the long-term. A new predictive nomogram and a web-based survival rate calculator we developed showed favorable applicability and accuracy to predict the long-term OS for DLBCL patients specifically. Keywords: Primary Central Nervous System Lymphoma (PCNSL), SEER, Treatment, Prognosis, Nomogram.